Research on deterministic computing power network - Qingmin JIA; Yujiao HU; Huayu ZHANG; Kailai PENG; Pingping CHEN; Renchao XIE; Tao HUANG (Tongxin xuebao)
In order to meet the development requirements of time-sensitive and computing-intensive businesses, the guarantee problem of real-time transmission and real-time computing of computing tasks was studied.Firstly, the research progress of computing power network and deterministic networking was briefly overviewed.Then, the technical scheme of deterministic computing power network was proposed, and the technical architecture and working mechanism were designed.Real-time transmission and real-time computing of computing tasks were realized through the technical capabilities such as computing-network perception, planning and scheduling, resource management and control.The simulation results also verified the effectiveness of the proposed technical scheme.Finally, the representative application scenarios of deterministic computing power network were analyzed, and the future development trends and technical challenges were discussed.